Tandem Substitutions in Somatic Hypermutation - Sepulveda Yañez, Julieta Haydee; Alvarez Saravia, Diego; Pilzecker, Bas; van Schouwenburg, Pauline A.; van den Burg, Mirjam; Veelken, Hendrik; Navarrete Signorile, Marcelo Alejandro; Jacobs, Heinz; Koning, Marvyn T. (My University, 2022)
Upon antigen recognition, activation-induced cytosine deaminase initiates affinity maturation of the B-cell receptor by somatic hypermutation (SHM) through error-prone DNA repair pathways. SHM typically creates single nucleotide substitutions, but tandem substitutions may also occur. We investigated incidence and sequence context of tandem substitutions by massive parallel sequencing of V(D)J repertoires in healthy human donors. Mutation patterns were congruent with SHM-derived single nucleotide mutations, delineating initiation of the tandem substitution by AID. Tandem substitutions comprised 5,7% of AID-induced mutations. The majority of tandem substitutions represents single nucleotide juxtalocations of directly adjacent sequences. These observations were confirmed in an independent cohort of healthy donors. We propose a model where tandem substitutions are predominantly generated by translesion synthesis across an apyramidinic site that is typically created by UNG. During replication, apyrimidinic sites transiently adapt an extruded configuration, causing skipping of the extruded base. Consequent strand decontraction leads to the juxtalocation, after which exonucleases repair the apyramidinic site and any directly adjacent mismatched base pairs. The mismatch repair pathway appears to account for the remainder of tandem substitutions. Tandem substitutions may enhance affinity maturation and expedite the adaptive immune response by overcoming amino acid codon degeneracies or mutating two adjacent amino acid residues simultaneously.
Keywords: apyrimidinic site; tandem dinucleotide substitutions (tdns); strand slippage; tandem substitution; translesion synthesis (tls); uracil-n-glycosylase (ung)